Almost Kenmotsu $f$-manifolds - Balkan, Y.S.; Aktan, N. (Carpathian Mathematical Publications, 2015)
In this paper, we consider a generalization of almost Kenmotsu f-manifolds. We get basic Riemannian curvature, sectional curvatures and scalar curvature properties such type manifolds. Finally, we give two examples to clarify some our results.